Innovation in takaful — what do Shariah advisors say about it? - Hassan, Rusni (REDmoney Group, 2019)
Innovation is an indispensable word in Takaful. Innovation here simply means the evolutionary process that alleviates the status quo of the industry for the better, offering a positive way on how things are done and uplifting the quality of life of people in general. Takaful is innovation in the field of insurance. It brings change in the status quo of insurance solutions for the people who previously had no other option other than conventional insurance.